Innate immunity against HIV: a priority target for HIV prevention research. - Borrow, P; Shattock, R; Vyakarnam, A (2010)
This review summarizes recent advances and current gaps in understanding of innate immunity to human immunodeficiency virus (HIV) infection, and identifies key scientific priorities to enable application of this knowledge to the development of novel prevention strategies (vaccines and microbicides). It builds on productive discussion and new data arising out of a workshop on innate immunity against HIV held at the European Commission in Brussels, together with recent observations from the literature.Increasing evidence suggests that innate responses are key determinants of the outcome of HIV infection, influencing critical events in the earliest stages of infection including the efficiency of mucosal HIV transmission, establishment of initial foci of infection and local virus replication/spread as well as virus dissemination, the ensuing acute burst of viral replication, and the persisting viral load established. They also impact on the subsequent level of ongoing viral replication and rate of disease progression. Modulation of innate immunity thus has the potential to constitute a powerful effector strategy to complement traditional approaches to HIV prophylaxis and therapy. Importantly, there is increasing evidence to suggest that many arms of the innate response play both protective and pathogenic roles in HIV infection. Consequently, understanding the contributions made by components of the host innate response to HIV acquisition/spread versus control is a critical pre-requisite for the employment of innate immunity in vaccine or microbicide design, so that appropriate responses can be targeted for up- or down-modulation. There is also an important need to understand the mechanisms via which innate responses are triggered and mediate their activity, and to define the structure-function relationships of individual innate factors, so that they can be selectively exploited or inhibited. Finally, strategies for achieving modulation of innate functions need to be developed and subjected to rigorous testing to ensure that they achieve the desired level of protection without stimulation of immunopathological effects. Priority areas are identified where there are opportunities to accelerate the translation of recent gains in understanding of innate immunity into the design of improved or novel vaccine and microbicide strategies against HIV infection.